2003
DOI: 10.1002/0471143030.cb1116s17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Chloroplast Protein Import

Abstract: This unit describes protocols for isolating chloroplasts from pea (Pisum sativum) and Arabidopsis thaliana for the study of nuclear‐encoded plastid precursor proteins. Chloroplasts from both preparations are competent for the in vitro import of recombinant preproteins synthesized using in vitro translation systems derived from reticulocyte or wheat germ lysates. These assays can be used to test whether a particular protein is targeted to chloroplasts, for analyzing the suborganellar location of newly imported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…For each import reaction, chloroplasts corresponding to 15 mg of chlorophyll and 6.5 mL of in vitrotranslated PPH preprotein were used. Lysis of chloroplasts, separation of stroma from membranes, and alkaline membrane treatment were done as described (Smith et al, 2002). All samples were resolved by SDS-PAGE and visualized using a phosphor imager (Bio-Rad).…”
Section: Protein Import Experimentsmentioning
confidence: 99%
“…For each import reaction, chloroplasts corresponding to 15 mg of chlorophyll and 6.5 mL of in vitrotranslated PPH preprotein were used. Lysis of chloroplasts, separation of stroma from membranes, and alkaline membrane treatment were done as described (Smith et al, 2002). All samples were resolved by SDS-PAGE and visualized using a phosphor imager (Bio-Rad).…”
Section: Protein Import Experimentsmentioning
confidence: 99%
“…Since transient expression of EGFP fusions of full-length Bs Toc159 or Bs Toc132 in B. sinuspersici ( Figure 2E) and Arabidopsis (Figures 4A and 4B) protoplasts produced identical subcellular localization patterns, we chose to express the EGFP fusion proteins in Arabidopsis protoplasts, due to the relative ease of subsequent chloroplast purification steps using standard and established protocols (Smith et al, 2002b) and given the intricate intracellular complexity of dimorphic chloroplast arrangement in B. sinuspersici. Fluorescence microscopy and immunoblot analysis of the subfractions from total transfected protoplasts and isolated chloroplasts showed that the full-length Toc159 fusion proteins were evenly distributed between the soluble and chloroplast membrane-associated fractions (Figures 4A and (C) Immunoblot analysis of endogenous Toc159 and Toc132 in subcellular fractions.…”
Section: Toc159 Cts Directed Egfp To the Chloroplast Envelopementioning
confidence: 99%
“…The chloroplast isolation procedures were modified from Smith et al (2002b). The isolated protoplasts of Arabidopsis and B. sinuspersici were pelleted by centrifugation (300g, 2 min) in an equal volume of W5 buffer (2 mM MES-KOH, pH 5.7, 154 mM NaCl, 125 mM CaCl 2 , and 5 mM KCl) and resuspended in 300 mL of HEPES-sorbitol buffer (50 mM HEPES-KOH, pH 7.3, and 330 mM sorbitol).…”
Section: Chloroplast Isolation From Isolated Protoplastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, chloroplasts were isolated from 15-to 20-d-old seedlings grown on 0.53 Murashige and Skoog plates supplemented with sucrose as described previously (Smith et al, 2002). Isolated intact chloroplasts were separated into membrane and soluble fractions by lysis in 0.1 M Na 2 CO 3 , pH 11.5, followed by centrifugation at 200,000g for 20 min.…”
Section: Plastid Fractionationmentioning
confidence: 99%